Effects of individual cognitive stimulation at home in adults with psychotic disorders - Justo-Henriques,Susana (2021)
Abstract We have seen an increase in the prevalence of mental disorders in Portugal. Despite this fact, the mental health care network is limited with no known home-based cognitive stimulation programs available. The aim of this study was to determine the effectiveness of an eight-month one-on-one cognitive stimulation intervention program in improving cognition, executive function and mood in adults with psychotic disorders (e.g., schizophrenia, delusional disorder). An uncontrolled repeated measures design was applied to 20 adults diagnosed with mental disorders who participated in 35 one-on-one sessions at home, conducted weekly, with 45 minutes each. Independent evaluators assessed cognitive status (MoCA), executive functions (FAB) and depressive symptoms (BDI). There was a significant effect of the intervention on cognitive status (d = 0.59), executive functions (d = 0.76) and depressive symptoms (d = 0.43). The results support sound effectiveness, viability and acceptability of the intervention in this mental health population.